2023
DOI: 10.1039/d2fo03171j
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds and functional foods as coadjuvant therapy for thrombosis

Abstract: Cardiovascular diseases (CVD) are the leading cause of death. The most common cardiovascular pathologies are thromboembolic diseases. The antithrombotic therapy prevents the thrombi formation or dissolves the previously constituted. However,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 102 publications
(160 reference statements)
0
1
0
Order By: Relevance
“…In fact, over the past few years, a number of structurally diverse plant molecules [ 30 , 31 ] and their derivatives have been found to have potential therapeutic effects [ 32 ], and some of them have been identified as antiviral molecules. In general, different studies have demonstrated the beneficial properties of culinary Mediterranean plants [ 33 , 34 ] and corresponding functional foods [ 35 , 36 , 37 ] with respect to several ailments. Some of them can strengthen the human body’s defenses against viral infections because they interfere with the life cycle of the virus or have beneficial effects on the host immunity [ 38 , 39 , 40 , 41 ], while others such as several steroidal glycosides including ouabain, digitoxin, and digoxin have shown in vitro a direct inhibitory activity against SARS-CoV-2 [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, over the past few years, a number of structurally diverse plant molecules [ 30 , 31 ] and their derivatives have been found to have potential therapeutic effects [ 32 ], and some of them have been identified as antiviral molecules. In general, different studies have demonstrated the beneficial properties of culinary Mediterranean plants [ 33 , 34 ] and corresponding functional foods [ 35 , 36 , 37 ] with respect to several ailments. Some of them can strengthen the human body’s defenses against viral infections because they interfere with the life cycle of the virus or have beneficial effects on the host immunity [ 38 , 39 , 40 , 41 ], while others such as several steroidal glycosides including ouabain, digitoxin, and digoxin have shown in vitro a direct inhibitory activity against SARS-CoV-2 [ 42 ].…”
Section: Introductionmentioning
confidence: 99%